2018
DOI: 10.1111/rode.12407
|View full text |Cite
|
Sign up to set email alerts
|

Mechanize or exit farming? Multiple‐treatment‐effects model and external validity of adoption impacts of mechanization among Nepalese smallholders

Abstract: The future of smallholders in developing countries is becoming increasingly uncertain in the face of rising farm wages. The custom-hiring of tractors, in which tractor owners provide non-owner farmers with land preparation and transport services for fees, has spread among smallholders in Asia, including Nepal. However, estimating the adoption impacts of agricultural mechanization by smallholders is complex as we must also take into account smallholders' options to exit farming. We investigate this issue by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Farm machines play an important role in sustainable and conservation agriculture development in emerging and developing countries [18,19,20,21]. A considerable body of literature has analyzed the impact of the use of farm machines on agricultural production [21,22,23,24,25]. For example, Benin [18] revealed that agricultural mechanization services used by farming households significantly increase farm yields in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Farm machines play an important role in sustainable and conservation agriculture development in emerging and developing countries [18,19,20,21]. A considerable body of literature has analyzed the impact of the use of farm machines on agricultural production [21,22,23,24,25]. For example, Benin [18] revealed that agricultural mechanization services used by farming households significantly increase farm yields in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…The value of household assets owned captures the overall household wealth that affects various behaviors, including liquidity constraints that affect investments in non-farm capitals, or risk-taking behaviors such as taking market risks and relying more on purchased food instead of subsistence food production (e.g., Takeshima 2018). Similarly, whether the commune received hunger elimination and poverty reduction program in the last three years is used to proxy the constraint due to poverty-trap or food-problem (or alleviation thereof), which often induces households to continue engaging in own-food production in a subsistence way (Schultz 1953).…”
Section: 22mentioning
confidence: 99%
“…More specifically, agricultural mechanization using tractors has significant impacts on labor productivity (Hamilton et al, 2022), farm efficiency (Huan et al, 2022), off‐farm income (Nguyen & Warr, 2020), land productivity (Zheng et al, 2021; Zhou et al, 2020), farm income growth (Kotu et al, 2023; Takeshima, 2018), off‐farm employment (Ma et al, 2018), and voluntary employment (Zhou & Ma, 2021). Moreover, in a study conducted in Myanmar, for example, agricultural mechanization enabled farmers to have incremental, overlapping, and complementary advantages such as labor savings, reduced drudgery, convenience, increased speed and timeliness of operations, improved ability to manage weather‐related risks, and reduced loss of grain during harvesting (Belton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study aims to assess labor shortages related to different farm activities, estimate the WTP for mechanization services, and identify policy options for promoting smallholder mechanization services in Malawi. Previous studies in SSA and Asia showed that smallholder farmers are willing to pay for tractor‐hire services for agricultural activities such as land preparation, weeding, harvesting, threshing, and transport (Hodjo et al, 2021; Houssou et al, 2016; Nxumalo et al, 2020; Takele & Selassie, 2018; Takeshima, 2018). To the best of our knowledge, however, no study has investigated smallholder farmers' WTP for agricultural mechanization services in Malawi.…”
Section: Introductionmentioning
confidence: 99%